Upaya Guru Pendidikan Agama Islam dalam Membentuk Akhlak Siswa - Iqbal, M (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract The study of Islamic education teachers' efforts in shaping student morals at MTsN 05 West Pasaman is very important to avoid the many problems regarding student morals that occur in this increasingly sophisticated era, with games on cellphones can change a person in terms of behavior. As well as many events that occur at school about a student who fights or commits acts of violence against the teacher. One of the cases regarding the dilapidation of student morals is the deadly persecution of a fine arts teacher. Through field studies, this research was conducted at MTsN 05 West Pasaman, which is located on Pematang Sontang Street, Sungai Aur District, West Pasaman Regency, West Sumatra Province with a zip code of 26573. The data collection techniques used are observation, interviews, documentation and triangulation or combined. This article suggests how the efforts of Islamic Religious Education teachers in shaping student morals at MTsN 05 West Pasaman. The findings of this study explain that Islamic Religious Education Teachers have efforts in shaping student morals which provide examples or examples, provide advice, enforce discipline, familiarize, provide motivation.Â AbstrakKajian terhadap upaya guru PAI dalam membentuk akhlak siswa di MTsN 05 Pasaman Barat ini sangat penting dilakukan untuk menghindarai banyaknya permasalahan mengenai akhlak siswa yang terjadi di era zaman yang semakin canggih ini, dengan game di handphone dapat merubah seseorang dalam segi berperilaku. Seperti halnya banyak yang terjadi peristiwa di sekolah tentang seorang siswa yang melawan maupun melakukan tindakan kekerasan terhadap guru. Salah satu kasus mengenai bobroknya akhlak siswa yaitu terjadi penganiayaan berujung maut terhadap guru seni rupa. Melalui studi lapangan, penelitian ini dilakukandi MTsN 05 Pasaman Barat yang berlokasi di Jalan Pematang Sontang Kecamatan Sungai Aur Kabupaten Pasaman Barat Provinsi Sumatra Barat dengan Kode pos 26573. Teknik pengumpulan data yang digunakan ialah melakukan observasi, wawancara, dukumentasi dan trianggulasi atau gabungan. Artikel ini mengemukakan bagaimana upaya guru pendidikan Agama Islam dalamÂ membentuk akhlak siswa di MTsN 05 Pasaman Barat. Adapun temuan penelitian ini menjelaskan bahwa Guru PAI mempunyai upaya dalam membetuk akhlak siswa dimana memberikan Contoh atau Teladan, Memberikan Nasihat, Menegakkan kedisiplinan, Membiasakan,Â Memberikan Motivasi.